Search for charged massive long-lived particles - Abazov, V. M. (2012)
We report on a search for charged massive long-lived particles (CMLLPs), based on 5.2fb -1 of integrated luminosity collected with the D0 detector at the Fermilab Tevatron pp̄ collider. We search for events in which one or more particles are reconstructed as muons but have speed and ionization energy loss (dE/dx) inconsistent with muons produced in beam collisions. CMLLPs are predicted in several theories of physics beyond the standard model. We exclude pair-produced long-lived gauginolike charginos below 267 GeV and Higgsino-like charginos below 217 GeV at 95% C.L., as well as long-lived scalar top quarks with mass below 285 GeV. © 2012 American Physical Society.